Education about Learning Motivation, Time Management, and Pocket Money Management for Students of Strada Bhakti Utama Junior High School - Ari Setiyaningrum; Lina Salim; Novia Utami (Journal of Innovation and Community Engagement, 2021)
Covid-19 pandemic has raised several problems faced by students including declining motivation to learn, lack of time to do independent assignments, and reduced amount of pocket money given by parents. This community service (CS) was designed to assist students in overcoming these problems through online education and training activities to increase students’ learning motivation and increase literacy on time management and pocket money management. Partners in this CS activity were 53 students of Strada Bhakti Utama Junior High School. The method of implementing activities used are counselling, exercises, and questions and answers. The success rate of this CS program was measured from analysis of the pre-test and post-test results conducted before and after the activity as well as from assessment of students' accuracy in answering online quiz questions. Based on results of pre-test and post-test analysis, CS activities through education and training on learning motivation, time management, and pocket money management were proven to be able to increase students' understanding of the importance of managing pocket money, saving, managing time, motivation, and source of motivators in life. In addition, based on the results of online quiz assessments, most students could answer correctly the questions about the material presented.